Maze solving balbot - Soon, Chi Wei (2010)
This paper concerns with the development of a two wheels balancing robot as the maze solver. This is a robot that uses sensors and DC gear motors on two wheels with inverted pendulum mechanism. The basic idea for a two wheels balancing robot is simple which is drive the wheels in the direction that the upper part of the robot is falling. If the wheels can be driven in such a way as to stay under the robot’s center of gravity, the robot remains balanced. The main purposes of this project are to construct a robot with the capability of balancing upright of two wheels and also as a maze solver robot. The GP2D120 IR distance sensor is used to achieve the balancing mode while the GP2D12 IR sensor is applied as the input for microcontroller in the determination of the path control algorithm. The path control algorithm will be coded in ATMEGA 32 microcontroller. The balancing robot will perform as a maze solver without losing the balancing functionality.